Voces en el crisol. Asedios a las reescrituras en Antígona Furiosa de Griselda Gambaro - Córdova Romero, Griselda (El Colegio de México, 2021)
This article explores the notion of rewriting in Griselda Gambaro’s Antigona furiosa (1986). In line with a long tradition of Antigones, her play appropriates the tragedy of Sophocles and reelaborates fragments taken from different texts by Marguerite Yourcenar, William Shakespeare, Rubén Darío, and from the last public speech made by Juan Domingo Perón. This broad panorama of textual dialogues is duly examined, but an analysis is also offered between Antígona furiosa and Leopoldo Marechal’s Antígona Vélez (1951). The aim here is to compare the mythical interpretation given to two key periods in the history of Argentina in the 20th century: Perón’s first presidency (1945-1955), and the terrorism carried out by the State during what was known as “El Proceso” (1976-1983). This study seeks to understand Gambaro’s theater as an artifact of memory, to point out the close relationship between her literature and the cultural, social and political world in which she moved in Argentina, as well as to highlight the central role of rewriting in this particular play.